Rancang Bangun Media Pembelajaran Komik Digital Pada Mata Pelajaran Desain Grafis Percetakan Berbasis Metode Interaktif Di SMKN 5 Telkom Banda Aceh - Suci Ning Trisnawati; Mira Maisura (Sekawan Institut, 2025)
The advancement of digital technology demands innovative and engaging learning media, especially in vocational education. This study aims to design an interactive digital comic for the Printing Graphic Design subject at SMKN 5 Telkom Banda Aceh, in response to the limited use of interactive media in classrooms. The research uses a Research and Development (R&D) approach with the ADDIE development model, limited to the development and expert validation stages. The media was built using Scratch, a platform that allows integration of animations, navigation, sound, and interactivity into a single learning tool, offering a contextual and dynamic experience. Validation by two media experts and two subject experts yielded average scores of 92.5% and 96.5%, respectively, categorized as “Strongly Agree,” indicating the media’s high feasibility. The study’s novelty lies in the use of Scratch—a platform rarely applied in vocational learning—for developing interactive comics. Compared to other tools that are mostly static or focused on passive visual design, Scratch provides greater flexibility in programming logic and user interaction, enhancing student engagement. The expected educational impact includes increased motivation, improved conceptual understanding, and strengthened digital literacy among vocational students. However, this study is limited to expert validation and does not include classroom implementation, so its effectiveness in real learning settings remains untested. Future research is recommended to evaluate the media’s impact on learning outcomes through classroom trials and explore the potential integration of technologies like Augmented Reality to further enhance interactivity and learning experiences.